Kaizen Application at The Reception Stage in a Sugarcane Plant - Filho, Manoel Gonçales; Barros, Marcos José; Campos, Fernando Celso de (Journal of Environmental Accounting and Management, 2026)
The main reasons for the decline of the sugar and alcohol sector in the last decade are the increased cost of production, delayed investment in the recovery of sugarcane plantations aiming higher production volumes, lack of competitiveness of ethanol and sugar and lack of investment in new technologies. This situation faced by the sugarcane industry in Piracicaba/ SP leads the sugarcane companies to seek increasingly competitiveness. This condition leads to continuous improvements, like the development of production systems. In this sense, a new operational and strategic orientation is needed to achieve the objective of profit maximization, and to excel in the current situation through an increase in productivity. In this paper, we intend to achieve the application of kaizen in the production process of a sugar and alcohol plant, specifically, at the reception of sugarcane. Therefore, this paper aims to apply the concept of lean manufacturing to maximize the yield of sugarcane reception process. The research method used was obtained in an exploratory literature review of the main concepts of lean production in order to provide the necessary basis for application of kaizen. A case study was carried out for the implementation of the concept. The contribution of this work is at pointing out improvements in the sugarcane reception process through a lean tool, the Current and Future Value Stream Mapping.